The preparation of the Ti-Al alloys based on intermetallic phases; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Kosova N.; Sachkov V. I. Viktor Ivanovich; Kurzina I.; Pichugina A.; Vladimirov A.; Kazantseva L.; Sachkova A. S. Anna Sergeevna (2016, 2016)
Title screen